(untitled) (Journal of Humanities, Social and Management Sciences (JHSMS-Asia), 2022)
Creating better citizens is one of the significant goals of education. Educational policies of Pakistan also stress on civic development of students as one of its essential goals. However, scholars have shown concerns about Pakistani students’ poor civic sense and teamwork skills. This current study aimed to examine the perspectives of local rural college students on civic responsibility and teamwork as outcomes of service-learning. Data were collected from 136 college students who participated in a service-learning project designed and implemented in Chitral Lower’s local college district. A questionnaire consisting of two scales: civic responsibility and teamwork, was used for data collection. The questionnaire was piloted before data collection. Experts checked content validity, and reliability was assessed by using Cronbach’s alpha. The principal component analysis technique was applied to analyse collected data with a principal component analysis approach. The results showed that respondents strongly agreed that service-learning significantly improved their sense of civic responsibility and teamwork skills. The results of this study extensively support the findings of previous research studies. However, it is suggested that the findings of this study may further be investigated in other contexts for a better understanding of the role of service-learning as civic and teamwork pedagogy.